(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The experiment was conducted to investigate the effects of blood meal supplement on growth performance and hematological parameters changes in broiler chicks. The experiment was carried out with 40 selected homogenous sex and weight broiler chicks having 10 for each group. The lay out of the study was conducted with control group A, fed only with standard commercial broiler ration and other groups viz. B, C, and D were fed with standard commercial ration in addition to 2.5 %, 5.0 %, and 7.5% blood meal supplement with water respectively for 15 days (21st to 35th days of age). The activities of broiler chicks, growth performance, weight loss or gain and any kind of abnormalities were closely observed in every day and the body weight was recorded at 7 days interval. During feeding of blood meal all treated groups were found increased body weight at different level.The blood meal supplied to the broiler chicks increased the growth performance that was directly proportional to the rate of blood meal supplement with water, because the ration was fixed for every group. In hematological observations, TEC, Hb concentration and PCV were decreased but rapid decreasing occurs in group (B) that was statistically significant (P<0.05). In this experiment during feeding of blood meal no clinical symptoms were found markedly. But slight symptoms occur when fed 7.5 % blood meal.The data were analyzed by least significance difference (LSD) with a compute program SPSS-11.50 (Statistical packages for social sciences). Keywords: Blood meal; Hematological parameters; Growth performance DOI: 10.3329/jbau.v6i2.4829 J. Bangladesh Agril. Univ. 6(2): 321-326, 2008